PENGARUH KENAIKAN BERAT BADAN BAYI BERAT LAHIR RENDAH YANG MENDAPAT KOMBINASI ASI-PASI - Imelda Fitri (Jurnal Ilmu Kebidanan, 2020)
Low Birth Weight Infant was the problem in all over world until nowdays because it causes illness and death on infant. The result of Indonesia Riskesdas in 2013 stated that presentage of toodlers (0-59 month) with low birth weight was the tenth sequence. This research aimed to know the influence of low birth weight infant increase that getting combination ASI-PASI in Arifin Achmad Genaral Hospital Pekanbaru. The type of research used analytic description that was quantitative, that conducted in Arifin Achmad General Hospital Pekanbaru on November 2015 until October 2016. The sample of research was 47 respondences, the instrument of research was scale of infant weight, the technique of collecting sample was by designing accidental sampling. The data was managed by computerization. The analysis of data used univariate and bivariate by using statistic nonparametric wilcoxon test. It was gained the distribution univariate result of female about 57.4 % and male was about 42.6 %, average of gestation age (34,5 weeks). The youngest gestation (28 weeks) and the oldest gestation (40 weeks). The result of statistic test was gained p=0,000 there was the significant difference between birth weight and wiegth after 14 days at the first caring on low birht weight baby that getting combination ASI-PASI with increase average of weight was amount 136,1 grams. It is suggested in order to raise exclusive ASI in fulfilling the nutrition need of baby especially low birth weight baby.